Adrenal incidentaloma: what is it? Review 1 - S.I. Rybakov (Mìžnarodnij Endokrinologìčnij Žurnal, 2021)
A review of the literature and the author’s own reflections are devoted to the issues of detecting various forms of pathology, which, being often benign, could exist for a long time, if not all life. The author proposes a definition of the term. Adrenal incidentaloma is a combined working category (group) that includes various forms of adrenal pathology, mainly neoplastic, benign or malignant, with or without signs of hormonal activity, as well as formations of inflammatory, infectious, parasitic origin, the consequences of trauma, developmental abnormalities that are found accidentally when examining patients for extra-adrenal diseases. The epidemiological aspects of the adrenal incidentalomas are considered. Basically, these are tumors of the adrenal cortex or medulla, tumor-like formations (cyst, inflammatory “tumor”, hematoma). Adrenal incidentalomas are accidentally found during examination of persons with diseases of the gastrointestinal tract, retroperitoneal space, kidneys, spine, chest, and small pelvis. Another source of adrenal incidentaloma detection is autopsy systemic data and, rarely, abdominal surgeries. The prevalence of adrenal incidentalomas reaches 2–6 %. The most objective data can be obtained from autopsy materials. The frequency of adrenal incidentalomas found in vivo depends on the type of imaging techniques used (ultrasound, computed tomography, magnetic resonance imaging), age, features of the surveyed populations, the presence of concomitant diseases (arterial hypertension, diabetes mellitus, etc.), and the qualifications of the researcher. Recently, clinical guidelines proposing a diagnostic and therapeutic algorithm have been published to help in clinical practice; however, several areas are still debatable and require further studies.